EVA versus Earnings: Does it Matter which is More Highly Correlated with Stock Returns? - Gerald T. Garvey; Todd T. Milbourn (Claremont McKenna College, Department of Economics, 2000)
Dissatisfaction with traditional accounting-based performance measures has spawned a number of alternatives, of which Economic Value Added (EVA) is clearly the most prominent. How can we tell which performance measures best capture managerial contributions to value? There is currently a heated debate among practitioners as to whether the new performance measures have a higher correlation with stock values and returns than do traditional accounting earnings. Academic researchers have instead relied on the variance of performance measures to gauge their relative accuracy. Our analysis pits EVA against earnings as two candidate performance measures. We use a relatively standard principal-agent model, but recognize that while the variability of each measure is observable, their exact information (signal) content is not. The model provides a formal method for ascertaining the relative value of such measures based on two distinct uses of the stock price. First, as is well-known, prices provide a noisy measure of managerial value-added. Our novel insight is that stock prices can also reveal the signal content of alternative accounting-based performance measures. We then show how to combine stock prices, earnings, and EVA to produce an optimally weighted compensation scheme. Surprisingly, we find that the simple correlation between EVA or earnings and stock returns is a reasonably reliable guide to their value as an incentive contracting tool. This is not because stock returns are themselves an ideal performance measure, rather it is because correlation places appropriate weights on both the signal and noise components of alternative measures. We then calibrate the theoretical improvement in incentive contracts from optimally using EVA in addition to accounting earnings at the firm and industry level. That is, we empirically estimate the 'value-added' of EVA by firm and industry. These estimates are positive and significant in predicting which firms have actually adopted EVA as an internal performance measure.
Keywords: 330